Evaluating the Effect of Syngas Composition on Micro gas turbine Performance - Fareeza N.; Tan E.S.; Kumaran P.; Indra T.M.; Fadzilah N.; Yoshikawa K. (Institute of Physics Publishing, 2023)
Carbon monoxide; Combustion; Fossil fuels; Nitric oxide; Synthesis gas; Co content; CO emissions; Combustion efficiencies; Hydrocarbon feedstock; Hydrogen contents; Micro gas turbines; Steady-state condition; Syngas composition; Gas turbines; carbon emission; carbon monoxide; combustion; fossil fuel; future prospect; hydrocarbon; hydrogen; natural gas; nitric oxide; performance assessment; research work; turbine